THE EFFECT OF BRAND ASSOCIATIONS, BRAND LOYALTY AND BRAND AWARENESS ON BRAND EQUITY ON SCARLETT WHITENING PRODUCTS (Case Study On Consumers Of Scarlett Whitening Products In Semarang City) - Innayah Hayyu Cahyati; Mulyo Budi Setiawan (Jurnal Ekonomi, 2022)
The purpose of this study was to determine the effect of brand associations, brand loyalty and brand awareness on brand equity in Scarlett Whitening products in Semarang City. The population in this study are consumers who have or are currently using scarlett whitening who live in the city of Semarang. With a sample of 100 respondents with a minimum age of 17 years. The method used in this research is purposive sampling method. The data analysis technique used in this study is multiple linear regression analysis assisted by the SPSS version 25 program. The results of this analysis show that brand associations have a positive and significant effect on brand equity, brand loyalty has a positive and significant effect on brand equity and brand awareness has a positive and significant effect on brand equity. significant to brand equity.